Uses of pedagogical cartography: bibliographic tracking of research in formal education - Forero-Mesa, Fabiola; Socha-Frontado, Diana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The present work makes an analysis of the uses of pedagogical cartography, focusing on scientific articles that record the experience of teachers in formal education, identifying how they have applied it, in those who have developed it and what social and educational implications it has had in the places where it has been implemented. A total of 90 publications were examined between 2017 and 2022, from different countries, identifying successes, findings, and opportunities presented by this methodology. The results indicate the advantage it has as a methodological strategy, for educational research and to build new knowledge within the academic and social context.